Evaluation of the Work of National Nature Parks: an Integrated Approach - Mykytyn, Taras; Yakymchuk, Alina; Tralo, Iryna (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/03/015, 2022)
National nature parks are the most common nature reserves in the world. These include protected areas that are part of the nature reserve fund of Ukraine. They allow free access to tourists. Usually, national parks preserve the historical and cultural heritage of the region, as well as are unique natural areas with picturesque nature. In Ukraine, 56 national nature parks have been created, covering an area of 1,399,161 hectares, which is 31% of the total area of the nature reserve fund. It is important to evaluate the work of national parks, to create a kind of a rating of these environmental institutions. There are different approaches to assessing the work of environmental institutions and methods that make it possible to assess the environmental safety of an enterprise. To determine the socio-ecological and economic assessment, we have adopted a methodology that allows us to consider the problems in the complex at each hierarchical level (micro-, meso-, macro-), identify risks of eco-destruction, forecast environmental changes under the influence of economic activity, assess economic opportunities development and ensuring acceptable quality of living conditions of people, human development under natural resource and environmental constraints. To calculate the proposed method, 9 indicators were used, which standardized and separately calculated the ecological status, socio-demographic status and economic status of national nature parks, as well as a comprehensive indicator. Calculations were made according to the proposed method for 2013. It was established that 4 parks have a high level of socio-ecological and economic security - Holosiivskyi, Buzkyi grad, Dermansko-Ostrozkyi, Vyzhnytskyi, sufficient – 17 parks, low – 18, critical – 3 parks (Podilsky Tovtry, Dvorichansky, Kremenets Mountains).